The Influence of Internal and External Factors on Increasing Youth’s Interest in Hydroponic Agribusiness in Kaliombo Sub-District, Kota Kediri - Purbowo, Muhammad Lukman; Astoko, Endro Puji; Helilusiatiningsih, Nunuk (Jurnal Manajemen Agribisnis dan Agroindustri, 2024)
The development of technology in the agricultural sector is so rapid that those who are left behind in utilizing technological advances will not get maximum benefits from their business activities. One of the developments in agricultural cultivation technology is hydroponic technology. The rapid development of agricultural technology is not comparable to the younger generation working in the agricultural sector. The younger generation is less interested in agricultural activities, including hydroponic technology. The purpose of this study is to describe the influence of internal and external factors in increasing the interest and aspirations of young people in hydroponic agribusiness in Kaliombo Village, Kediri City District, and to analyze the influence of internal and external factors on the interest and aspirations of young people in hydroponic agribusiness in Kaliombo Village, Kediri City District. The data analysis used in this study used the Likert Rating Scale (SLR) and multiple regression analysis. The multiple linear regression equation in this study is written as Y = 2.476 + 0.142X1 + 0.072X2 + e. The results of the study on the influence of internal and external factors on increasing the interest of young people in hydroponic agribusiness in Kaliombo Village, Kediri City District obtained the following conclusions; internal and external factors that have been carried out by young people in Kaliombo Village, Kediri City District together have played a major role in the interest and aspirations of young people in hydroponic agribusiness in Kaliombo Village, Kediri City District, internal factors owned by young people influence the interest of young people in hydroponic agribusiness.